Isolation and identification of cellular stress proteins associated with boid inclusion body disease - Ilyasu, Yusuf Maina (2016)
Boid inclusion body disease is one of the fatal and most important diseases of captive boid snakes worldwide. Till today, cases were diagnosed by the demonstration of eosinophilic intracytoplasmic inclusion bodies from tissue sections under light microscopy. However, inclusion bodies are also found in many other viral infections. Understanding the specific etiologic agent and the disease pathogenesis has eluded researchers for over three decades since the disease was first discovered in the 1970s. Recently however, highly divergent and novel arenaviruses were isolated from tissues of snakes with the disease. Even though the arenaviruses isolated were novel and highly divergent in each case, researchers were able to establish causal linkage with the disease in vitro. Research has now focused on understanding the formation and nature of the inclusion protein commonly found in tissues of affected snakes. It is believed that understanding the nature and the chemical composition of this protein may lead to a better understanding of the cause, progression and diagnosis of the disease. Various cellular stress proteins have frequently been found as common component of cellular response to viral infections associated with protein aggregation. A proteomic profile of such proteins can be used to understand the disease pathogenesis leading to a better understanding of the disease diagnosis and consequently its treatment. The present study therefore attempts to shed some light towards further understanding the pathogenesis of BIBD in snakes through a comparative study of the protein profiles from BIBD infected and healthy specimens by means of electrophoresis and peptide mass spectrometry. Tissue samples obtained at necropsy from snakes that died naturally of the disease as well as those obtained from experimentally infected chicken embryos were subjected to total protein isolation using PRO-PREPTM protein isolation solution according to the manufacturer’s protocol and quantified by the Bradford method. Protein separation was accomplished through SDS-PAGE, and the protein bands of various sizes were purified, trypsin-digested and identified by mass spectrometry. The peptide sequences obtained were analysed using the Mascot sequence matching software [Matrix Science] with Ludwig NR database. The peptide sequences were compared against known protein sequences on the data base. Fourteen proteins were identified from the infected specimens using peptide mass finger printing with matrix-assisted laser desorption/ionization-time of flight-mass spectrometry, twelve out of which were heat shock proteins. These were heat shock protein 5 (hsp5), heat shock cognate protein 71 (hsc71) and glucose regulatory protein 78 (grp78) with protein hit score values greater than 32 significantly different at (p<0.05). Specimens from the BIBD negative snake did not show these proteins in their profile. Specimens from the chicken embryo showed inclusion bodies at histopathology in their tissues, but did not yield any protein band on the electrophoretogram. Heat shock protein 70 family have frequently been associated with protein aggregation diseases and because of the known role they play in the progression of such diseases, the study therefore added some knowledge that may help in understanding the pathogenesis of BIBD in snakes. The study also confirms that BIBD-associated pathogen can be propagated in embryonated chicken egg, a finding that might be of immense benefit to laboratories and diagnostic facilities that have interest in the study of this virus but lack cell culture capabilities for its propagation.